AN EXPERIMENTAL STUDY OF THE BEHAVIOUR OF INTERFACE SHEARING BETWEEN FINE GRAINED SOILS AND STEEL (Sciences & Technologie. B, Sciences de l'ingénieur, 2004)
The shear strength, when large displacements occur, at the interface between two types of clays and steel has been studied in the ring shear apparatus. The results obtained indicate that the surface roughness and the average diameter of particles have a significant effect on the interfacial shear strength.. According to roughness, two shearing modes are likely to take place: shearing at the interface and shearing within the soil. For soil- soil shearing, the "pre-sheared" clay shear strength is likely to be either equal (neutral effect) or greater (positive effect) than that obtained for not pre-sheared samples. However, in interface tests, the clays tested may exhibit neutral, positive or negative effect.